Effects of a plyometric training program in sub-elite futsal players during pre-season period - Branquinho, L.; Ferraz, R.; Teixeira, J.; Neiva, H. P.; Sortwell, A.; Forte, P.; Marinho, D. A.; Marques, M. C. (International Journal of Kinesiology & Sports Science, 2022)
Background of Study: Plyometric training (PT) programs can improve several motor skills during the pre-season. Even so, its impact during the pre-season specifically in futsal remains unclear. Objective: The present observational study examines the impact of a six-week PT program that included varied strength exercises in adult male futsal players. Method: Fourteen futsal players from a Portuguese men`s sub-elite team that competed in a national championship (mean ± Standard deviation (SD) age: 25.78±7.05 years) were included in this cross-sectional study that analyzed the consequences of a PT program during the pre-season, followed by four weeks of detraining. Players were monitored 3 times: at the beginning, after six weeks of PT and four weeks after the end of PT. Results: The current research presented significant mean changes with the application of the training program in the three assessment moments for agility (small to moderate effect), countermovement jump (CMJ) height (trivial to small effect), and sprint performance (trivial to moderate large effect). When assessing the mean differences between pre- and post-training, the differences are more evident in their magnitude (? = -12.73 to 3.69%, d = 0.38 to 2.08). Furthermore, the PT program showed the greatest influence on 20 m sprint with a large effect (? = -12.73%, d = 2.08), followed by a small and moderate effect for agility (? = -6.46%, d = 0.85) and for the 10 m sprint (? = -3.53%, d = 0.38). Conclusions: These results confirmed the impact of a six-week plyometric training during the pre-season in sub-elite futsal players. This new evidence can be particularly useful in pre-season planning in futsal.